Where Claxton Falls Short: The Illusions of Consumption Addiction - Savage, Joshua (Stance: an international undergraduate philosophy journal, 2019)
Guy Claxton suggests that post-Industrial Revolution westerners are consumption addicts and argues that we must embrace a more frugal and environmentally considerate lifestyle. However, I argue that Claxton’s analysis and solution to consumption addiction does not penetrate far enough. Through Warren’s ecofeminist reasoning and Heidegger’s notion of technology, I show that the anthropocentric assumption inherent in western consumption engenders a destructive and oppressive worldview by creating the illusion that we are justified in subordinating non-human entities.